PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MACROMEDIA AUTHORWERE 7.0 TERHADAP AKTIVITAS DAN MINAT BELAJAR PADA ANAK BERKEBUTUHAN KHUSUS DI SD INKLUSIF - Hermawan Wahyu Setiadi, Fembriarto (Universitas PGRI Yogyakarta, 2017)
The aims of this research is to analyze the difference of (1) the significant study activity subject of interactive media-based Macromedia Authorware 7.0 and students who followed conventional learningmodel, (2) the significant difference of natural science learning interest between students who followinteractive media-based Macromedia Authorware 7.0 and those who follow conventional learning model,(3) the difference of activity and learning interest natural science simultaneously between students whofollow interactive media-based Macromedia Authorware 7.0 and those who follow conventional learningmodel. The populations in research were all fourth grade students of Al Firdaus School academic year2016/2017 with a sample amount of 91 students. The data of learning study activity were collected usingobservation technique and learning interest were collected using questionnaire. The data were analyzedby using descriptive statistic and MANOVA. The research result shows that: (1) there is difference ofstudy activity between students who followed interactive media-based Macromedia Authorware 7.0 andstudents who followed conventional learning model (2) there is difference of natural science learninginterest between students who followed interactive media-based Macromedia Authorware 7.0 andstudents who followed conventional learning model (3) there is a difference of study activity and naturalscience learning interest simultaneously between students who followed interactive media-basedMacromedia Authorware 7.0 and students who followed conventional learning. Key Words: Study activity, Interactive media-based Macromedia Authorware 7.0, Learning interest